Board Chairmen’s Involvement in the Nomination and Remuneration Committees and Earnings Management - Mujeeb Saif Mohsen Al-Absy; Ku Nor Izah Ku Ismail; Sitraselvi Chandren (Australasian Accounting, Business and Finance Journal, 2019)
A board chairman is a very influential figure in a firm which may be dominated by an insider director, who, in some cases, is a family member. Consequently, the board chairmen (BC) may play a vital role in the firm’s output, especially when they sit on the board committees. Therefore, the current study aims to examine the influence of the BC who are also: the chairmen of the nomination committee (BCNDUAL); ordinary members of the nomination committee (BCNMEM); the chairmen of the remuneration committee (BCRDUAL); and ordinary members of the remuneration committee (BCRMEM), on the level of accrual earnings management (AEM) and real earnings management (REM). This study also tests the overall influence of the BC’s involvement in the nomination committee (BCNINV) by combining the terms of BCNDUAL and BCNMEM into BCNINV and the overall influence of BC’s involvement in the remuneration committee (BCRINV) by combining the terms of BCRDUAL and BCRMEM into BCRINV, on the level of AEM and REM. This study selected 300 firms listed on the Bursa Malaysia Main Market with the lowest positive performance (based on return on assets (ROA)) for the years 2013 to 2015. The random-effects feasible generalized least squares (FGLS) regression shows that BCNDUAL, BCNMEM and BCNINV have a significant positive relationship with AEM and REM. However, BCRDUAL and BCRINV have a significant negative relationship with AEM but not with REM. This study aims to alert policy makers, firms and their stakeholders, as well as researchers of the need to strengthen their board committees’ effectiveness (especially the nomination committee), and to make them more independent.
Keywords: Board chairmen; nomination committee; remuneration committee; earnings management; Malaysia.